2017
DOI: 10.1002/ijgo.12118
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a pregnant patient with systemic lupus erythematosus with uterine atony and very thin myometrium with uterine fibrosis

Abstract: A pregnant patient with systemic lupus erythematosus experienced hypertension and underwent cesarean delivery. They experienced uterine atony and a very thin myometrium with uterine fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…As such, the present study supports the recommendation of minimizing the total steroid dose by utilizing combined regimens with other immunosuppressive agents (17). Studies have also reported that high-dose steroids can increase the risk of placenta accreta formation and uterine myometrial brosis due to reduced estrogenic effect and endometrial thinning, potentially causing atonic bleeding and substantial blood loss (18,19). Thus, minimizing the total steroid dose whenever possible is crucial to ensure optimal outcomes for both the mother and fetus.…”
Section: Discussionsupporting
confidence: 82%
“…As such, the present study supports the recommendation of minimizing the total steroid dose by utilizing combined regimens with other immunosuppressive agents (17). Studies have also reported that high-dose steroids can increase the risk of placenta accreta formation and uterine myometrial brosis due to reduced estrogenic effect and endometrial thinning, potentially causing atonic bleeding and substantial blood loss (18,19). Thus, minimizing the total steroid dose whenever possible is crucial to ensure optimal outcomes for both the mother and fetus.…”
Section: Discussionsupporting
confidence: 82%
“…SLE is an autoimmune disorder that develops mainly in women of reproductive age and sometimes becomes life-threatening. 16 In addition to the known risks of perinatal events in patients with SLE, some recent reports demonstrated that cases of unresponsiveness to oxytocin 17 18 and excessive uterine atony due to a very thin myometrium 18 19 20 (both present in our patient) were observed in patients with SLE. Moreover, Noh et al reported a case of spontaneous rupture of an unscarred uterus at 23 weeks of gestation in a woman with SLE with long-term steroid treatment.…”
Section: Discussionsupporting
confidence: 52%
“…They observed uterine fibrosis in a patient with SLE who received long-term steroid treatment, and suggested that uterine fibrosis might have caused PPH in the patient. 18 In our case, the patient had taken prednisolone 5 mg/day for 11 years which was considered long-term steroid treatment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…There were 12 reports (7 English and 5 Japanese articles), and 14 patients were identified, including our patient. Interestingly, all patients were from Asian counties (Japan [ 3 , 4 , 7 ]), South Korea [ 2 , 6 ] Vietnam [ 5 ]. Here, we reviewed eight patients from 6 English articles, including our patients with SLE during pregnancy with uterine wall thinning and PAS (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%